A technique for removing wildfowl viscera for research - Harrison, Jeffery G (Wildfowl, 1960)
In July, 1957, Dr. Geoffrey Matthews and I published an article on 'Duck Viscera for Scientific Research' in the Shooting Times for the benefit of wildfowlers, who were to supply the basic material for the proposed food and parasitic surveys of wildfowl to be undertaken by the Wildfowl Trust. My part in that article was to produce a practical method of extracting the viscera from a duck without spoiling the bird in any way for the table. The method had been worked out experimentally on a small number of duck obtained towards the end of the previous season, but since then the technique has been perfected and as the results are proving of such value, it would seem useful to record the method in some detail for others to follow or modify.